Influence of temperature and water to poultry waste ratio on methane production from anaerobic digestion - Hasmi, Hazwani; Buyong, Faieza (International Journal of Engineering and Technology, 2018)
The operating temperature and water to poultry waste ratio in anaerobic digestion process are among the factors that affect methane production. Therefore, this paper aimed to investigate the influence of temperature and water to poultry waste ratio on anaerobic digestion of poultry waste. In this study, three different temperatures were used; psychrophilic (25 Â°C), mesophilic (35 Â°C) and thermophilic (55 Â°C), while two different water to poultry waste ratio were examined; 1: 1 and 2: 1 (water: poultry waste). The methane production was the highest at mesophilic temperature followed by psychrophilic and thermophilic temperature with cumulative amount of methane at 14.99 x 10-3 L, 0.62 x 10-3 L and 0.22 x 10-3 L respectively. The highest methane production was observed at the water to poultry waste ratio of 2: 1 followed by ratio 1: 1 with cumulative amount of methane production at 0.11 x 10-3 L and 0.05 x 10-3 L.Â Â